Investigation of Thermal Stress In Different Metal Based Dental Restorations By Mathematical Analysis - Faik Tugut; Hakan Akin; Mehmet Coskun; Tahsin Boyraz (Cumhuriyet Dental Journal, 2015)
Purpose: The aim of this study is to investigate the effect of heat changes in oral environment that produce thermal stresses (TS) in prosthetic restorations by mathematical method.Material and Methods: Three different metallic frameworks in gold alloy, commercial pure titanium (cpTi) and chrome-cobalt- molybdenum (CrCoMo) and the ceramics, Ticeramics for cpTi, Omega900 for CrCoMo and VM13 for Au alloys were used for mathematical modeling. The physical properties were obtained from the manufactures. The calculation method was based on Boley’s equation.Results: In ceramics the highest thermal stress was in Ticeramic and the lowest was in VM13. At interface of the restoration thermal stress accumulation was the highest in cpTi and Ticeramic and the lowest was in Au and VM13. In metallic substructures CrCoMo shows the highest and Au had the lowest thermal stress depositon in its structures.Conclusion: Thermal stresses are not cable off breaking the metal-ceramic bond strength but shorten the life span of the prosthetics.Key Words: Thermal stress, Dental materials, Ceramics, Titanium